PARADIGMA PENDIDIKAN UNTUK PEMBANGUNAN YANG BERKELANJUTAN DI TONGYEONG-SI, GYEONGSANGNAMDO, KOREA SELATAN - Hastangka Hastangka (Jurnal Filsafat "WISDOM", 2016)
Education for sustainable development has become global paradigm recently. This paradigm is a form of dynamic response and debate faced by the global community such as global warming, energy crisis, climate change, food security, as well as environmental damage. The main idea, in this paradigm was put in three main principles which are to build environmental, socio-economic and cultural sustainability. This study aims to explore and describe how the paradigm in Tongyeong-si, Gyeongsangnamdo, South Korea. This research focuses on the basic philosophical paradigm and implementation of education for sustainable development at a school in the city of Tonyeong (Tongyeong-si), Gyeongsangnamdo, South Korea. The results indicate that the basic philosophy applied in education for sustainable development in the Tongyeong is formed community who have a concern for the environment has its base in the reconstruction of the society will be able to change the surrounding community. This educational paradigm can contribute in strengthening aspects of character education and awareness of the environment for future generations with the support of actors from the government and society through an integrated approach to policy and program activities that are on going, so it has an impact and benefits for better society.